KONSEP ETIKA PENDIDIK DALAM PENDIDIKAN ISLAM MENURUT PEMIKIRAN SYAIKH IMAM AN-NAWAWI AD-DAMASYQI DAN HADRATUS-SYAIKH K.H. MUHAMMAD HASYIM ASY’ARI - Adawi’ah, Frida Robi’ah; Arini, Aida; Muslih, imam (EL-Islam, 2023)
Abstract: Currently the problem of good character has become a matter of concern, the need for Islamic Education. It is very important to study the ethics of educators.This study aims to rewiew how the concept of educator ethics in Islamic Education according to the thoughts of Syaikh Imam an-Nawawi ad-Damasyqi, to rewiew how the concept of educator ethics in Islamic education according to the thought of Hadratus-Syaikh K.H. Muhammad Hasyim Asyâ€™ari, to rewiew how the similarities and differences in the concept of educator ethics in Islamic education according to the thoughts of Imam an-Nawawi ad-Damasyqi and Hadratus-Syaikh K.H. Muhammad Hasyim Asyâ€™ari.The research method used is library research with data analysis, namely content analysis and comparative analysis. The type of research is literature, character thinking. Based on the results of the study, they are summarized as follows:1)The concept of educator ethics in Islamic education according to the thoughts of Syaikh Iamm an-Nawawi ad-Damasyqi:a. Personal Educator Ethics,b. Ethics of Educators when Teaching,c.Educator Ethics towards Students.2)According to Hadratus-Syaikh K.H. Muhammad Hasyim Asyâ€™ari:a. Personal Educator Ethics,b. Ethics of Educators when Teaching,c.Educator Ethics towards Students.(3)The similarity is the personal ethics of educators: Feeling found by Allah SWT, having noble behavior with despicable morals, not putting knowledge, practicing sunah practices, and reading prayers, lies in having â€œIntentionsâ€.The similarity of educator ethics his face, before strating the lesson to read a few verses of the Quran. The difference is in purifying the body and mind. The similarities between educators ethics towards students:Must have straight intentions,the difference:advise students